Composite demulsifier for dehydrating oily scum and oily scum treatment process
The composite deemulsion agent prepared by loading ruthenium-doped carbon doped on porous aluminum-doped manganese dioxide, combined with ultrasonic technology, solved the problem of poor dehydration effect of oil-containing scum, achieved efficient oil-water separation and crude oil recovery, and improved the wastewater treatment effect.
Patent Information
- Application Number
- CN202411644746.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The prior art has limited dehydration effect when treating oil-containing scum and is difficult to recover crude oil, which increases the burden on hazardous waste treatment for enterprises and wastes crude oil resources.
A composite deemulsion agent is used, which is prepared by loading ruthenium-doped carbon doped on porous aluminum-doped manganese dioxide, combined with ultrasonic technology for dehydration of oil-containing scum.
It achieves efficient demulsification and dehydration, promotes oil-water separation, improves crude oil recovery, and improves the wastewater treatment effect through strong oxidative degradation of COD.
Smart Images

Figure CN119161089B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of oily scum and water treatment, and in particular to a composite demulsifier for dehydrating oily scum and an oily scum treatment process. Background Art
[0002] Refinery scum refers to the oily sludge produced when oil droplets and solid particles in the water are attached to tiny air bubbles and carried to the water surface after flocculants are added to the flotation section of the wastewater treatment process of petrochemical enterprises. It is mainly composed of negatively charged hydrophilic colloidal particles, with complex composition and difficult to dehydrate. As the quality of crude oil deteriorates, the amount of scum will increase significantly. At present, enterprises generally mix scum with other oil sludge and add flocculants. After mechanical separation and dehydration, the water content is reduced to about 85% and then landfilled as hazardous waste. Due to the serious emulsification of scum, the dehydration effect of the existing process is limited, and crude oil recovery is difficult, which not only increases the burden of hazardous waste treatment for enterprises, but also wastes crude oil resources.
[0003] There are three main methods for demulsification of scum, namely physical method, chemical method and biological method. Among them, the physical method mainly includes gravity sedimentation method, centrifugal separation method, filtration method, electric field method, microwave radiation method, ultrasonic method and membrane demulsification method, etc.; the chemical method mainly includes demulsifier addition method.
[0004] The ultrasonic method is to radiate ultrasonic energy into the crude oil emulsion to produce a series of ultrasonic effects, such as stirring, collision, aggregation, cavitation, heating, negative pressure, etc., so as to destroy the oil-water interface film. It can still play the role of demulsification, desalination and dehydration without or with a small amount of demulsifier. Since ultrasound has good conductivity in both oil and water, this method is suitable for various types of emulsions. For water-in-oil emulsified crude oil produced by tertiary oil recovery, wastewater recovery oil, aged oil, etc., due to the complexity of their chemical composition and emulsion structure, it is difficult to use conventional methods to demulsify, desalinate and dehydrate. The sonochemical method can be used for the desalination and dehydration of such oils, and has good results (Li Shuqin, Cheng Yongqing, Zhang Xumin. Study on the sonochemical method for demulsification and dehydration of water-containing crude oil [J]. Tianjin Chemical Industry, 1997, 4: 22-24.).
[0005] Adding demulsifier is a chemical dehydration method, which mainly utilizes the displacement effect of demulsifier. After the demulsifier is added, it diffuses toward the oil-water interface. Since the interfacial activity of the demulsifier is higher than that of the film-forming substances in the crude oil, it can adsorb or partially replace the natural emulsifier adsorbed on the oil-water interface, and form a mixed film with the film-forming substances in the crude oil with a lower interfacial film strength than the original interfacial film, resulting in the destruction of the interfacial film, releasing the water encapsulated in the film, and the water droplets gather together to form large water droplets that settle to the bottom, and the oil and water phases separate, achieving the purpose of demulsification (Kotsaridou. Demulsifyingwater-in-oil emulsions through chemical addition [J]. Erdoel Erdgas Kohle, 1996, 112(2): 72-79.).
[0006] The demulsification effect of current demulsifiers needs to be further improved, and a single demulsification method is often difficult to achieve satisfactory results, so it is necessary to develop a demulsification scheme that combines multiple methods and further treat the wastewater and scum after demulsification. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a composite demulsifier for dehydrating oily scum and a process for treating oily scum in view of the deficiencies in the above-mentioned prior art.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is: In the first aspect of the present invention, a composite demulsifier for dehydrating oily scum is provided, which is prepared by the following method:
[0009] S1. Preparation of porous aluminum-doped manganese dioxide Al-MnO 2 ;
[0010] S2. One-pot hydrothermal method in Al-MnO 2 The composite demulsifier is obtained by loading ruthenium-doped carbon dots on it:
[0011] S2-1, take aminoacridine yellow, citric acid, acetic acid, ethylenediamine, RuCl 3 ·3H 2 O is added into a mixed solution consisting of ethanol and deionized water, and ultrasonically dispersed to obtain a precursor solution A;
[0012] S2-2, taking porous aluminum-doped manganese dioxide and adding it into deionized water, and ultrasonically dispersing it to obtain a precursor solution B;
[0013] S2-3, adding the precursor solution A to the precursor solution B under stirring, stirring, transferring the obtained mixture to a reaction kettle, heating and performing a hydrothermal reaction, filtering after the reaction, washing and drying the solid product, and obtaining the composite demulsifier, recorded as Al-MnO 2 @Ru-CDs;
[0014] The composite demulsifier is used for dehydration treatment of oily scum, and is assisted by applying ultrasonic waves during use.
[0015] Preferably, step S1 specifically comprises:
[0016] Manganese acetate and aluminum nitrate nonahydrate are added to an ethanol aqueous solution composed of ethanol and deionized water, and then ammonium bicarbonate is added for ultrasonic dispersion. The resulting mixed solution is transferred to a reactor and reacted under heating. After the reaction is completed, the solid product is filtered, washed, dried, and then calcined to obtain porous aluminum-doped manganese dioxide: Al-MnO 2 .
[0017] Preferably, step S1 specifically comprises:
[0018] 0.57-2.25 g of manganese acetate and 0.17-0.75 g of aluminum nitrate nonahydrate are added to 100-400 mL of an ethanol aqueous solution composed of ethanol and deionized water in a volume ratio of 1:1, and then 0.16-0.64 g of ammonium bicarbonate is added, and ultrasonic dispersion is performed for 30-90 min. The resulting mixed solution is transferred to a polytetrafluoroethylene-lined reactor, and the reaction is performed at 155-180 ° C for 6-18 h. After the reaction is completed, the mixture is cooled to room temperature, filtered, and the solid product is washed with deionized water, dried at 70-110 ° C to constant weight, and then calcined at 350-450 ° C for 1-4 h, and cooled to room temperature to obtain porous aluminum-doped manganese dioxide: Al-MnO 2 .
[0019] Preferably, step S2 specifically comprises:
[0020] S2-1, take 291-1164 mg aminoacridine yellow, 384-1536 mg citric acid, 120-480 mg acetic acid, 45-180 mg ethylenediamine, 52-208 mg RuCl 3 ·3H 2 O is added into a mixed solution consisting of 50-200 mL of ethanol and 25-100 mL of deionized water, and ultrasonically dispersed for 3-20 min to obtain a precursor solution A;
[0021] S2-2, take 0.5-2g of porous aluminum-doped manganese dioxide and add it into 50-200mL of deionized water, and disperse it by ultrasonic for 5-30min to obtain precursor solution B;
[0022] S2-3, the precursor solution A is added to the precursor solution B under stirring, and the mixture is stirred at 500-2000 rpm for 15-60 min. The obtained mixture is transferred to a polytetrafluoroethylene-lined reactor, and the reaction is carried out at 160-200° C. for 6-24 h. After the reaction is completed, the mixture is cooled to room temperature and filtered. The solid product is washed with deionized water and vacuum dried at 70-100° C. for 6-24 h to obtain the composite demulsifier, which is recorded as Al-MnO 2 @Ru-CDs.
[0023] Preferably, the composite demulsifier for dehydrating oil scum is prepared by the following method:
[0024] S1. Preparation of porous aluminum-doped manganese dioxide Al-MnO 2 :
[0025] 1.145 g of manganese acetate and 0.375 g of aluminum nitrate nonahydrate were added to 200 mL of an ethanol aqueous solution composed of ethanol and deionized water in a volume ratio of 1:1, and then 0.32 g of ammonium bicarbonate was added, and ultrasonic dispersion was performed for 45 min. The resulting mixed solution was transferred to a polytetrafluoroethylene-lined reactor and reacted at 165 ° C for 10 h. After the reaction was completed, it was cooled to room temperature and filtered. The solid product was washed with deionized water, dried at 100 ° C to constant weight, and then calcined at 400 ° C in an air atmosphere for 2 h, and cooled to room temperature to obtain porous aluminum-doped manganese dioxide: Al-MnO 2 ;
[0026] S2. One-pot hydrothermal method in Al-MnO 2 The composite demulsifier is obtained by loading ruthenium-doped carbon dots on it:
[0027] S2-1, take 582 mg of aminoacridine yellow, 768 mg of citric acid, 240 mg of acetic acid, 90 mg of ethylenediamine, 104 mg of RuCl 3 ·3H 2 O was added into a mixed solution consisting of 100 mL of ethanol and 50 mL of deionized water, and ultrasonically dispersed for 5 min to obtain precursor solution A;
[0028] S2-2, take 1g of porous aluminum-doped manganese dioxide and add it into 100mL of deionized water, and disperse it by ultrasonic for 15min to obtain precursor solution B;
[0029] S2-3, the precursor solution A was added to the precursor solution B under stirring, and the mixture was stirred at 1000 rpm for 30 min. The obtained mixture was transferred to a polytetrafluoroethylene-lined reactor and reacted at 180°C for 12 h. After the reaction was completed, the mixture was cooled to room temperature and filtered. The solid product was washed with deionized water and vacuum dried at 90°C for 12 to obtain the composite demulsifier, which was recorded as Al-MnO 2 @Ru-CDs.
[0030] The second aspect of the present invention provides a process for treating oily scum, which uses the composite demulsifier as described above to dehydrate the oily scum with the assistance of ultrasonic waves.
[0031] Preferably, the oily scum treatment process comprises the following steps:
[0032] 1) Alkalization of oily scum:
[0033] 2) Composite demulsifier and ultrasonic combined demulsification and dehydration:
[0034] A composite demulsifier is added to the oily scum after alkalization treatment, stirred, and then ultrasonic waves are applied. After ultrasonic waves, the mixture is allowed to stand for stratification. The lower aqueous phase is scum wastewater, which is subjected to wastewater post-treatment after separation; the upper oil phase contains oily scum, which is subjected to scum post-treatment after separation.
[0035] Preferably, the oily scum treatment process comprises the following steps:
[0036] 1) Alkalization of oily scum:
[0037] Adding Na to the oily scum 2 CO 3 and stirring evenly, adjusting the pH value of the oily scum to 7-8 to obtain the oily scum after alkalization treatment;
[0038] 2) Composite demulsifier and ultrasonic combined demulsification and dehydration:
[0039] The oily scum after alkalization treatment is injected into a container, a composite demulsifier with a mass concentration of 0.25-1% is added, and the mixture is stirred at 400-1200 rpm for 10-30 min, and then heated to 50-70°C, and ultrasonic standing waves are applied with a frequency of 10-40 kHz and an ultrasonic power of 200-350 W, and the ultrasonic treatment time is 3-10 min;
[0040] After ultrasound, the mixture was allowed to stand for stratification. The lower layer was scum wastewater containing a composite demulsifier, which was subjected to wastewater post-treatment after separation. The upper oil phase was preliminarily dehydrated oily scum, which was subjected to scum post-treatment after separation.
[0041] Preferably, the wastewater post-treatment method is:
[0042] Add 100-200 mL / L H 2 O 2 Then apply ultrasonic standing wave, the frequency is 30-65kHz, the ultrasonic power is 300-400W, and the ultrasonic treatment time is 30-90min; filter, recover the filter residue, and the filtrate is the treated wastewater.
[0043] Preferably, the scum post-treatment method is:
[0044] The initially dehydrated oily scum obtained in step 2) is separated into oil, water and mud residue in a three-phase horizontal spiral centrifuge, the oil phase product and the water phase product are recycled, and the mud residue product is discharged for further post-processing.
[0045] The beneficial effects of the present invention are:
[0046] The invention provides a composite demulsifier for dehydrating oily scum and an oily scum treatment process based on the composite demulsifier combined with ultrasound. Under the combined action of the composite demulsifier and ultrasound, physical and chemical multiple demulsification can be achieved to promote efficient dehydration of the oily scum.
[0047] The composite demulsifier of the present invention is obtained by in-situ loading of ruthenium-doped carbon dots on porous aluminum-doped manganese dioxide. The composite demulsifier itself has strong oxidizing properties, and by means of the sonic sensitivity of the ruthenium-doped carbon dots, it can efficiently generate active oxygen under the action of ultrasound, showing excellent oxidizing ability. It can achieve efficient demulsification in the early dehydration operation stage, and can achieve efficient removal of COD in the later scum wastewater treatment stage; at the same time, since the composite demulsifier has a porous structure, it can also provide physical adsorption at the same time.
[0048] The composite demulsifier in the present invention exhibits strong oxidizing properties under the assistance of ultrasound, and can oxidize and degrade the dirty oil coated on the water surface, destroy the stable mixture formed by oil and water, and thus promote oil-water separation; and during the demulsification process, the stirring, collision, aggregation, cavitation, heating, negative pressure and other effects generated by ultrasound can also destroy the oil-water interface film to achieve demulsification. Therefore, in the present invention, the ultrasound in the demulsification operation link can achieve demulsification mainly through physical effects on the one hand, and on the other hand, it can assist the ruthenium-doped carbon dots to achieve chemical demulsification through strong oxidation. The combination of the two aspects can significantly improve the demulsification effect.
[0049] In the oil-containing scum treatment process of the present invention, the scum is firstly subjected to alkalization treatment, and then demulsification is carried out by combining a composite demulsifier with ultrasound, and the stratification is carried out by gravity sedimentation, wherein the lower layer is scum wastewater containing the composite demulsifier, and the upper oil phase is the preliminarily dehydrated oil-containing scum; the scum wastewater containing the composite demulsifier is further subjected to the action of ultrasound, and the organic components in the water are degraded by means of the strong oxidizing ability improved by the composite demulsifier; the preliminarily dehydrated oil-containing scum is subjected to three-phase separation by a three-phase horizontal spiral centrifuge, and the oil phase product is recovered, and finally the resource treatment of the scum is realized, which can reduce environmental pollution, recover useful resources, and form obvious economic benefits and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 The test results of the active oxygen generation performance test in the present invention;
[0051] Figure 2 is the XRD pattern of the composite demulsifier prepared in Example 1-1;
[0052] Figure 3 The test results of the moisture content of Example 2 and Comparative Example 2 are shown below:
[0053] Figure 4 The test results of COD removal rate of Example 2 and Comparative Example 2 are shown in FIG.
[0054] Figure 5 The test results of oil recovery rate of Example 2 and Comparative Example 2 are shown;
[0055] Figure 6 The test results of the effect of ultrasonic action time on the water content in the initial dehydrated oily scum;
[0056] Figure 7 The test results show the influence of ultrasonic power on the water content in the initial dehydration of oily slag. DETAILED DESCRIPTION
[0057] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0058] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0059] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0060] The present invention provides a composite demulsifier for dehydrating oily scum, which is prepared by the following method:
[0061] S1. Preparation of porous aluminum-doped manganese dioxide Al-MnO 2 :
[0062] 0.57-2.25 g of manganese acetate and 0.17-0.75 g of aluminum nitrate nonahydrate are added to 100-400 mL of an ethanol aqueous solution composed of ethanol and deionized water in a volume ratio of 1:1, and then 0.16-0.64 g of ammonium bicarbonate is added, and ultrasonic dispersion is performed for 30-90 min. The resulting mixed solution is transferred to a polytetrafluoroethylene-lined reactor, and the reaction is performed at 155-180 ° C for 6-18 h. After the reaction is completed, the mixture is cooled to room temperature, filtered, and the solid product is washed with deionized water, dried at 70-110 ° C to constant weight, and then calcined at 350-450 ° C for 1-4 h, and cooled to room temperature to obtain porous aluminum-doped manganese dioxide: Al-MnO 2 .
[0063] S2. One-pot hydrothermal method in Al-MnO 2 The composite demulsifier is obtained by loading ruthenium-doped carbon dots on it:
[0064] S2-1, take 291-1164 mg aminoacridine yellow, 384-1536 mg citric acid, 120-480 mg acetic acid, 45-180 mg ethylenediamine, 52-208 mg RuCl 3 ·3H 2 O is added into a mixed solution consisting of 50-200 mL of ethanol and 25-100 mL of deionized water, and ultrasonically dispersed for 3-20 min to obtain a precursor solution A;
[0065] S2-2, take 0.5-2g of porous aluminum-doped manganese dioxide and add it into 50-200mL of deionized water, and disperse it by ultrasonic for 5-30min to obtain precursor solution B;
[0066] S2-3, the precursor solution A is added to the precursor solution B under stirring, and the mixture is stirred at 500-2000 rpm for 15-60 min. The obtained mixture is transferred to a polytetrafluoroethylene-lined reactor, and the reaction is carried out at 160-200° C. for 6-24 h. After the reaction is completed, the mixture is cooled to room temperature and filtered. The solid product is washed with deionized water and vacuum dried at 70-100° C. for 6-24 h to obtain the composite demulsifier, which is recorded as Al-MnO 2 @Ru-CDs.
[0067] The composite demulsifier is used for dehydration treatment of oily scum, and is assisted by applying ultrasonic waves during use.
[0068] The composite demulsifier of the present invention is obtained by in-situ loading of ruthenium-doped carbon dots on porous aluminum-doped manganese dioxide. It has strong oxidizing properties, and by virtue of the sonic sensitivity of ruthenium-doped carbon dots, it can efficiently generate active oxygen under ultrasound, showing excellent oxidizing ability, and can achieve efficient demulsification in the early dehydration operation section, and can achieve efficient removal of COD in the later scum wastewater treatment stage; at the same time, since the composite demulsifier has a porous structure, it can also provide physical adsorption at the same time. The preparation method and mechanism of action are described in detail below to facilitate the understanding of the present invention.
[0069] The present invention first uses manganese acetate as a manganese source, aluminum nitrate nonahydrate as an aluminum source, and ammonium bicarbonate as a pore-enlarging agent, and combines conventional hydrothermal reaction with calcination to prepare porous aluminum-doped manganese dioxide with a rich pore structure;
[0070] Then, aminoacridine yellow, citric acid, acetic acid, and ethylenediamine were used as the main raw materials, and RuCl 3 ·3H 2 O is the doping component, and Ruthenium-doped carbon dots are in situ grafted onto porous aluminum-doped manganese dioxide by a one-pot hydrothermal method to obtain a composite demulsifier. In this process, the pore structure of porous aluminum-doped manganese dioxide is very important for Ru 3+ The adsorption effect is generated, and the hydroxyl groups on the porous aluminum-doped manganese dioxide surface can react with Ru 3+ Produce electrostatic attraction and coordination, Ru 3+ At the same time, it can also coordinate with the carboxyl group, amino group, etc. in the raw material components, so that these components can be evenly loaded on the porous aluminum-doped manganese dioxide, and then the ruthenium-doped carbon dots are synthesized by hydrothermal reaction. 3+ The uniform loading of carbon dots on porous aluminum-doped manganese dioxide can be promoted during the preparation process.
[0071] In the composite demulsifier of the present invention, the manganese element in the manganese dioxide is in a relatively high valence state and has oxidizing properties; and the manganese dioxide contains abundant active centers, which can adsorb reactants and promote the oxidative degradation of organic matter. The porous structure of manganese dioxide provides a large number of adsorption sites, so that it has a strong adsorption capacity for various pollutants. Aluminum doping can change the morphology of manganese dioxide, so that it has more nano-needle structures, thereby exposing more active sites and enhancing its activity. Aluminum has excellent high temperature resistance and strength. When doped in manganese dioxide with a porous structure, it can improve the stability of the pore structure, reduce the collapse of pores during calcination, and help increase the specific surface area.
[0072] In the composite demulsifier of the present invention, the ruthenium-doped carbon dots have a good inheritance of the sono-thermal sensitivity of aminoacridine yellow, and can efficiently generate active oxygen under the action of ultrasound; the doped ruthenium will produce ruthenium oxide (RuO 2) itself has a high oxidizing property. At the same time, due to the change of electronic structure caused by Ru doping, new surface energy can be formed, active sites can be increased, the sonic sensitivity effect of carbon dots can be enhanced, and the efficiency of active oxygen generation can be enhanced, thereby significantly improving the oxidizing property of the composite demulsifier.
[0073] The composite demulsifier in the present invention is mainly based on the oxidative demulsification mechanism. The working principle of oxidative demulsification is mainly to destroy the emulsifier in the emulsion through oxidation reaction; in the emulsion, the emulsifier reduces the oil-water interfacial tension so that the oil and water can form a stable mixture; and the oxidative demulsifier can undergo redox reaction with the emulsifier, making the emulsifier inactive, thereby reducing the stability of the emulsion. The composite demulsifier in the present invention exhibits strong oxidizing properties under the assistance of ultrasound, which can oxidize and degrade the dirty oil coated on the water surface, destroy the stable mixture formed by oil and water, and thus promote oil-water separation; and in the demulsification process, the stirring, collision, aggregation, cavitation, heating, negative pressure and other effects generated by ultrasound can also destroy the oil-water interface film and achieve demulsification. Therefore, in the present invention, the ultrasound in the demulsification operation link can achieve demulsification mainly through physical effects on the one hand, and on the other hand, it can assist ruthenium-doped carbon points to achieve chemical demulsification through strong oxidation. The combination of the two aspects can significantly improve the demulsification effect.
[0074] Furthermore, the strong oxidizing property of the composite demulsifier can efficiently degrade COD in the subsequent scum wastewater treatment stage. Therefore, in addition to playing a role in oxidative degradation of oil film in the demulsification operation section, the composite demulsifier can also play a role in oxidative degradation of COD in the subsequent scum wastewater further treatment process.
[0075] The present invention also provides a process for treating oily scum, which uses the composite demulsifier as described above to dehydrate the oily scum with the assistance of ultrasonic waves.
[0076] The process includes the following steps:
[0077] 1) Alkalization of oily scum:
[0078] Adding Na to the oily scum 2 CO 3 and stirring evenly, adjusting the pH value of the oily scum to 7-8 to obtain the oily scum after alkalization treatment;
[0079] 2) Composite demulsifier and ultrasonic combined demulsification and dehydration:
[0080] The oily scum after alkalization treatment is injected into a container, a composite demulsifier with a mass concentration of 0.25-1% is added, and the mixture is stirred at 400-1200 rpm for 10-30 min, and then heated to 50-70°C, and ultrasonic standing waves are applied with a frequency of 10-40 kHz and an ultrasonic power of 200-350 W, and the ultrasonic treatment time is 3-10 min;
[0081] After ultrasound, the mixture was allowed to stand for stratification. The lower layer was scum wastewater containing a composite demulsifier, which was subjected to wastewater post-treatment after separation. The upper oil phase was preliminarily dehydrated oily scum, which was subjected to scum post-treatment after separation.
[0082] Among them, the wastewater post-treatment method is:
[0083] Add 100-200 mL / L H 2 O 2 , then apply ultrasonic standing wave, frequency 30-65kHz, ultrasonic power 300-400W, ultrasonic treatment time 30-90min; filter, recover the filter residue, and the filtrate is the treated wastewater. The treated wastewater can be further treated with other post-treatments, such as biochemical treatment, according to the actual situation. The recovered filter residue mainly contains composite demulsifier, which can be regenerated to recycle the composite demulsifier.
[0084] Among them, the slag post-treatment method is:
[0085] The initially dehydrated oily scum obtained in step 2) is separated into oil, water and mud residue in a three-phase horizontal spiral centrifuge, the oil phase product and the water phase product are recycled, and the mud residue product is discharged for further post-processing.
[0086] The present invention firstly performs alkalization treatment on the scum, then demulsifies by combining a composite demulsifier with ultrasound, and separates the scum by gravity sedimentation, wherein the lower layer is scum wastewater containing the composite demulsifier, and the upper oil phase is the preliminarily dehydrated oil-containing scum;
[0087] The scum wastewater containing the composite demulsifier is further degraded by the strong oxidizing ability of the composite demulsifier under the action of ultrasound; the initial dehydrated oily scum is separated into three phases by a three-phase horizontal spiral centrifuge, and the oil phase product is recovered, finally realizing the resource treatment of the scum, which can not only reduce environmental pollution, but also recover useful resources, forming obvious economic and environmental benefits.
[0088] Among them, since the oily scum is the oily sludge produced by the addition of flocculants in the flotation section of the wastewater treatment process of petrochemical enterprises, the oil droplets and solid particles in the water are attached to tiny air bubbles and are carried to the water surface, so there will be flocculants in the mud residue products. These flocculants can be further recovered through relevant subsequent treatment processes.
[0089] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.
[0090] Example Group 1
[0091] Example 1-1
[0092] A composite demulsifier for dehydrating oil scum is prepared by the following method:
[0093] S1. Preparation of porous aluminum-doped manganese dioxide Al-MnO 2 :
[0094] 1.145 g of manganese acetate and 0.375 g of aluminum nitrate nonahydrate were added to 200 mL of an ethanol aqueous solution composed of ethanol and deionized water in a volume ratio of 1:1, and then 0.32 g of ammonium bicarbonate was added. Ultrasonic dispersion was performed for 45 min, and the resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and reacted at 165 ° C for 10 h. After the reaction was completed, it was cooled to room temperature and filtered. The solid product was washed with deionized water, dried at 100 ° C to constant weight, and then calcined at 400 ° C for 2 h (in air atmosphere), and cooled to room temperature to obtain porous aluminum-doped manganese dioxide: Al-MnO 2 ;
[0095] S2. One-pot hydrothermal method in Al-MnO 2 The composite demulsifier is obtained by loading ruthenium-doped carbon dots on it:
[0096] S2-1, take 582 mg of aminoacridine yellow, 768 mg of citric acid, 240 mg of acetic acid, 90 mg of ethylenediamine, 104 mg of RuCl 3 ·3H 2 O was added into a mixed solution consisting of 100 mL of ethanol and 50 mL of deionized water, and ultrasonically dispersed for 5 min to obtain precursor solution A;
[0097] S2-2, taking 0.75 g of porous aluminum-doped manganese dioxide and adding it into 100 mL of deionized water, and ultrasonically dispersing it for 15 min to obtain precursor solution B;
[0098] S2-3, the precursor solution A was added to the precursor solution B under stirring, and the mixture was stirred at 1000 rpm for 30 min. The obtained mixture was transferred to a polytetrafluoroethylene-lined reactor and reacted at 180° C. for 12 h. After the reaction was completed, the mixture was cooled to room temperature and filtered. The solid product was washed with deionized water and vacuum dried at 90° C. for 12 h to obtain the composite demulsifier, which was recorded as Al-MnO 2 @Ru-CDs.
[0099] Example 1-2
[0100] The difference between this example and Example 1 is that:
[0101] In step S2-2, 1 g of porous aluminum-doped manganese dioxide is added.
[0102] Examples 1-3
[0103] The difference between this example and Example 1 is that:
[0104] In step S2-2, 1.25 g of porous aluminum-doped manganese dioxide was added.
[0105] Comparative Example Group 1
[0106] Comparative Example 1-1
[0107] S1. Preparation of porous manganese dioxide MnO 2 :
[0108] 1.145 g of manganese acetate was added to 200 mL of an ethanol aqueous solution composed of ethanol and deionized water in a volume ratio of 1:1, and then 0.32 g of ammonium bicarbonate was added. Ultrasonic dispersion was performed for 45 min. The resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and reacted at 165 ° C for 10 h. After the reaction was completed, it was cooled to room temperature and filtered. The solid product was washed with deionized water, dried at 100 ° C to constant weight, and then calcined at 400 ° C for 2 h (in air atmosphere), and cooled to room temperature to obtain porous manganese dioxide: MnO 2 ;
[0109] S2, one-pot hydrothermal method in MnO 2 The composite demulsifier is obtained by loading ruthenium-doped carbon dots on it:
[0110] S2-1, take 582 mg of aminoacridine yellow, 768 mg of citric acid, 240 mg of acetic acid, 90 mg of ethylenediamine, 104 mg of RuCl 3 ·3H 2 O was added into a mixed solution consisting of 100 mL of ethanol and 50 mL of deionized water, and ultrasonically dispersed for 5 min to obtain precursor solution A;
[0111] S2-2, take 0.75g of porous manganese dioxide and add it into 100mL of deionized water, and disperse it by ultrasonic for 15min to obtain precursor solution B;
[0112] S2-3, the precursor solution A was added to the precursor solution B under stirring, and the mixture was stirred at 1000 rpm for 30 min. The obtained mixture was transferred to a polytetrafluoroethylene-lined reactor and reacted at 180° C. for 12 h. After the reaction was completed, the mixture was cooled to room temperature and filtered. The solid product was washed with deionized water and vacuum dried at 90° C. for 12 h to obtain the composite demulsifier, which was recorded as MnO 2 @Ru-CDs.
[0113] Comparative Example 1-2
[0114] A composite demulsifier for dehydrating oil scum is prepared by the following method:
[0115] S1. Preparation of porous aluminum-doped manganese dioxide Al-MnO 2 , the specific steps are the same as those in Example 1-1;
[0116] S2. One-pot hydrothermal method in Al-MnO 2 The carbon dots are loaded on the surface to obtain a composite demulsifier:
[0117] S2-1, add 582 mg of aminoacridine yellow, 768 mg of citric acid, 240 mg of acetic acid, and 90 mg of ethylenediamine into a mixed solution consisting of 100 mL of ethanol and 50 mL of deionized water, and disperse by ultrasonic for 5 minutes to obtain a precursor solution A;
[0118] S2-2, taking 0.75 g of porous aluminum-doped manganese dioxide and adding it into 100 mL of deionized water, and ultrasonically dispersing it for 15 min to obtain precursor solution B;
[0119] S2-3, the precursor solution A was added to the precursor solution B under stirring, and the mixture was stirred at 1000 rpm for 30 min. The obtained mixture was transferred to a polytetrafluoroethylene-lined reactor and reacted at 180° C. for 12 h. After the reaction was completed, the mixture was cooled to room temperature and filtered. The solid product was washed with deionized water and vacuum dried at 90° C. for 12 h to obtain the composite demulsifier, which was recorded as Al-MnO 2 @CDs.
[0120] Active oxygen generation performance test:
[0121] The composite demulsifiers prepared in Examples 1-1, 1-2, 1-3 and Comparative Examples 1-1 and 1-2 were tested for their ability to generate active oxygen according to the following method:
[0122] The composite demulsifier was added to deionized water and ultrasonically dispersed to prepare a dispersion with a concentration of 0.2 mg / mL. Ultrasonic standing waves were applied at a frequency of 50 kHz and an ultrasonic power of 350 W. The reactive oxygen species fluorescent probe (ROS Brite 570, Ex (nm) 554Em (nm) 568, Xi'an Baiying Biotechnology Co., Ltd.) was used to measure the reactive oxygen species content at different treatment times. The higher the fluorescence intensity, the higher the reactive oxygen species content.
[0123] Test results such as Figure 1 As shown, it can be seen that Examples 1-2, 1-2, and 1-3 can all efficiently generate active oxygen under ultrasound. The reason for the decrease in the active oxygen generation efficiency in Comparative Example 1 is that aluminum is not doped in manganese dioxide, which affects the stability and porosity of the composite demulsifier, affects the loading of carbon dots, and reduces the number of active sites. The decrease in the active oxygen generation efficiency in Comparative Example 2 indicates that the doping of ruthenium in carbon dots can improve the ability of the composite demulsifier to generate active oxygen under ultrasound.
[0124] The XRD pattern of the composite demulsifier prepared in Example 1-1 is as follows: Figure 2 As shown, it illustrates the successful preparation of the composite demulsifier.
[0125] Example Group 2
[0126] The following embodiment group is a process for treating oily scum using different composite demulsifiers. The oily scum used is the oily scum from the flotation section of Yangzhou Petrochemical Co., Ltd. (flocculant is added to the flotation section). The scum has a water content of 97%, an oil content of 5‰, a volume average particle size of 28.3 μm, and a specific surface area of 0.62 m 2 ·g -1 .
[0127] Example 2-1
[0128] A process for treating oily scum, which uses the composite demulsifier prepared in Example 1-1 to dehydrate the oily scum, and the process comprises the following steps:
[0129] 1) Alkalization of oily scum:
[0130] Adding Na to the oily scum 2 CO 3 and stirring evenly, adjusting the pH value of the oily scum to 7.25 to obtain the oily scum after alkalization treatment;
[0131] 2) Composite demulsifier and ultrasonic combined demulsification and dehydration:
[0132] The oily scum after alkalization treatment was injected into a container, and a composite demulsifier with a mass concentration of 0.5% was added, stirred at 800 rpm for 15 min, and then heated to 60 ° C, and ultrasonic standing waves were applied with a frequency of 20 kHz and an ultrasonic power of 300 W. The ultrasonic treatment time was 6 min.
[0133] After ultrasound, the mixture was allowed to stand for stratification. The lower layer was scum wastewater containing composite demulsifier, which was subjected to wastewater post-treatment after separation. The upper oil phase was preliminarily dehydrated oily scum, which was subjected to scum post-treatment after separation.
[0134] 3) Wastewater post-treatment method is:
[0135] Add 150 mL / L H 2 O 2 Then, ultrasonic standing wave is applied with a frequency of 50 kHz, an ultrasonic power of 350W, and an ultrasonic treatment time of 45min; the filter is filtered, the filter residue is recovered, and the filtrate is the treated wastewater;
[0136] 4) Post-treatment of scum:
[0137] The initially dehydrated oily scum obtained in step 2) is separated into oil, water and mud residue in a three-phase horizontal spiral centrifuge, the oil phase product and the water phase product are recycled, and the mud residue product is discharged for further post-processing.
[0138] Performance Testing
[0139] 1. According to the method of Example 2-1, the composite demulsifiers prepared in Example 1-2, Example 1-3, Comparative Example 1-1, and Comparative Example 1-2 are replaced to dehydrate the oily scum, which are recorded as Example 2-2, Example 2-3, Comparative Example 2-1, and Comparative Example 2-2 in sequence; the following treatment indicators are calculated:
[0140] 1. The water content ηw of the preliminary dehydrated oily scum obtained in step 2);
[0141] 2. Detect the COD content of the scum wastewater before treatment and the COD content of the treated wastewater obtained after treatment in step 3), and calculate the COD removal rate;
[0142] 3. The recovery rate ηo of the oil phase product in step 4);
[0143] The determination of water content refers to GB / T 260-2016 "Determination of water content of petroleum products - Distillation method".
[0144] Determination of oil content: The solution in the distillation flask is filtered through pre-weighed filter paper and collected in a 100 mL beaker. The distillation flask and the filter paper are placed in an oven and dried at 105 °C to constant weight. The weight difference before and after is the solid phase weight. The oil content of the scum is obtained by the differential weight method.
[0145] Determination of COD: Determine the COD of wastewater according to “Water Quality-Determination of Chemical Oxygen Demand-Sealed Catalytic Digestion Method” (HZ-HJ-SZ-0108).
[0146] The test results are shown in Table 1 below:
[0147] Table 1
[0148]
[0149] From the test results in Table 1, it can be seen that too little (Example 2-3) and excessive (Example 2-1) carbon point loading in the composite demulsifier are not conducive to demulsification and COD removal under ultrasonic action; and the doping of aluminum in manganese dioxide can improve the performance of the composite demulsifier, and the doping of ruthenium in the composite demulsifier has a significant enhancing effect on improving COD removal.
[0150] 2. According to Example 2-2, the ultrasonic action time was changed to test the water content in the preliminary dehydrated oily scum.
[0151] Test results such as Figure 3 As shown in the figure, it can be seen that within a certain range (0-6min), as the ultrasonic time increases, the water content gradually decreases, but as the ultrasonic radiation time further increases, the water content of the scum will gradually increase, and the dehydration effect will deteriorate. This is because the scum contains a large amount of solid particles and dirty oil. The mechanical vibration of the ultrasound changes the surface structure of the particles, reduces the adsorption capacity of the particles to oil, and makes it easier to peel off from the particle surface; the oil droplets collide and aggregate with each other to form oil droplets with larger particle size, which are easy to separate from water. As the ultrasonic time increases, the total energy input into the system continues to increase, which in turn breaks up the aggregated oil droplets and re-integrates them into water, promoting the emulsification of the oil droplets, resulting in a deterioration of the dehydration effect (Wang Hongping. Research on droplet motion and coalescence characteristics under ultrasonic action [D]. Beijing: China University of Petroleum (Beijing), 2014.). Too short or too long ultrasonic time is not conducive to the dehydration of scum. The relative optimal ultrasonic time is determined to be 6 min.
[0152] 3. According to Example 2-2, the ultrasonic power was changed to test the water content in the preliminary dehydrated oily scum to study the effects of ultrasonic action time and ultrasonic power on demulsification and dehydration.
[0153] Test results such as Figure 4As shown in the figure, it can be seen that with the increase of acoustic power, the water content of the scum after treatment first decreases and then increases. There is an optimal value of ultrasonic power in the process of ultrasonic dehydration. This is because with the increase of acoustic power, the corresponding ultrasonic sound intensity is also increasing. When the ultrasonic sound intensity exceeds the cavitation threshold, cavitation will occur, forming a new emulsification of the waste oil, which increases the difficulty of dehydrating the waste oil.
[0154] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A composite demulsifier for dehydrating oily scum, characterized in that: It is prepared by the following method: S1. Preparation of porous aluminum-doped manganese dioxide Al-MnO2; S2. One-pot hydrothermal method was used to load ruthenium-doped carbon dots on Al-MnO2 to obtain a composite demulsifier: S2-1, add aminoacridine yellow, citric acid, acetic acid, ethylenediamine, and RuCl3·3H2O into a mixed solution consisting of ethanol and deionized water, and disperse by ultrasonic to obtain a precursor solution A; S2-2, taking porous aluminum-doped manganese dioxide and adding it into deionized water, and ultrasonically dispersing it to obtain a precursor solution B; S2-3, adding the precursor solution A to the precursor solution B under stirring, stirring, transferring the obtained mixture to a reaction kettle, performing a hydrothermal reaction under heating, filtering after the reaction, washing and drying the solid product, and obtaining the composite demulsifier, recorded as Al-MnO2@Ru-CDs; The composite demulsifier is used for dehydration of oily scum, and is used to assist in applying ultrasonic waves; Step S1 is specifically as follows: Take 0.57-2.25g of manganese acetate and 0.17-0.75g of aluminum nitrate nonahydrate and add them to 100-400mL of ethanol aqueous solution composed of ethanol and deionized water in a volume ratio of 1:1, then add 0.16-0.64g of ammonium bicarbonate, ultrasonically disperse for 30-90min, transfer the obtained mixed solution to a polytetrafluoroethylene-lined reactor, react at 155-180°C for 6-18h, cool to room temperature after the reaction, filter, wash the solid product with deionized water, dry at 70-110°C to constant weight, and then calcine at 350-450°C in an air atmosphere for 1-4h, cool to room temperature, and obtain porous aluminum-doped manganese dioxide: Al-MnO2.
2. The composite demulsifier for dehydrating oil scum according to claim 1, characterized in that: Step S2 is specifically as follows: S2-1, add 291-1164 mg of aminoacridine yellow, 384-1536 mg of citric acid, 120-480 mg of acetic acid, 45-180 mg of ethylenediamine, and 52-208 mg of RuCl3·3H2O into a mixed solution consisting of 50-200 mL of ethanol and 25-100 mL of deionized water, and disperse by ultrasonic for 3-20 min to obtain a precursor solution A; S2-2, take 0.5-2g of porous aluminum-doped manganese dioxide and add it into 50-200mL of deionized water, and disperse it by ultrasonic for 5-30min to obtain precursor solution B; S2-3. Add precursor solution A to precursor solution B under stirring, stir at 500-2000 rpm for 15-60 min, transfer the resulting mixture to a polytetrafluoroethylene-lined reactor, react at 160-200°C for 6-24 h, cool to room temperature after the reaction, filter, wash the solid product with deionized water, and vacuum dry at 70-100°C for 6-24 h to obtain the composite demulsifier, recorded as Al-MnO2@Ru-CDs.
3. The composite demulsifier for dehydrating oil scum according to claim 2, characterized in that: It is prepared by the following method: S1. Preparation of porous aluminum-doped manganese dioxide Al-MnO2: 1.145 g of manganese acetate and 0.375 g of aluminum nitrate nonahydrate were added to 200 mL of an ethanol aqueous solution composed of ethanol and deionized water in a volume ratio of 1:1, and then 0.32 g of ammonium bicarbonate was added, and ultrasonic dispersion was performed for 45 min. The resulting mixed solution was transferred to a polytetrafluoroethylene-lined reactor and reacted at 165 ° C for 10 h. After the reaction was completed, it was cooled to room temperature and filtered. The solid product was washed with deionized water, dried at 100 ° C to constant weight, and then calcined at 400 ° C in an air atmosphere for 2 h, and cooled to room temperature to obtain porous aluminum-doped manganese dioxide: Al-MnO2; S2. One-pot hydrothermal method was used to load ruthenium-doped carbon dots on Al-MnO2 to obtain a composite demulsifier: S2-1, add 582 mg of aminoacridine yellow, 768 mg of citric acid, 240 mg of acetic acid, 90 mg of ethylenediamine, and 104 mg of RuCl3·3H2O into a mixed solution consisting of 100 mL of ethanol and 50 mL of deionized water, and disperse by ultrasonic for 5 minutes to obtain a precursor solution A; S2-2, take 1g of porous aluminum-doped manganese dioxide and add it into 100mL of deionized water, and disperse it by ultrasonic for 15min to obtain precursor solution B; S2-3. Precursor solution A is added to precursor solution B under stirring, and the mixture is stirred at 1000 rpm for 30 min. The resulting mixture is transferred to a polytetrafluoroethylene-lined reactor and reacted at 180°C for 12 h. After the reaction is completed, the mixture is cooled to room temperature and filtered. The solid product is washed with deionized water and vacuum dried at 90°C for 12 to obtain the composite demulsifier, which is recorded as Al-MnO2@Ru-CDs.
4. A process for treating oily scum, which comprises dehydrating the oily scum by using the composite demulsifier as claimed in any one of claims 1 to 3 with the assistance of ultrasonic waves.
5. The oily scum treatment process according to claim 4, characterized in that: The following steps are involved: 1) Alkalization of oily scum: 2) Composite demulsifier and ultrasonic combined demulsification and dehydration: A composite demulsifier is added to the oily scum after alkalization treatment, stirred, and then ultrasonic waves are applied. After ultrasonic waves, the mixture is allowed to stand for stratification. The lower aqueous phase is scum wastewater, which is subjected to wastewater post-treatment after separation; the upper oil phase contains oily scum, which is subjected to scum post-treatment after separation.
6. The oily scum treatment process according to claim 5, characterized in that: The following steps are involved: 1) Alkalization of oily scum: Adding Na2CO3 to the oily scum and stirring evenly, adjusting the pH value of the oily scum to 7-8, and obtaining the oily scum after alkalization treatment; 2) Composite demulsifier and ultrasonic combined demulsification and dehydration: The oily scum after alkalization treatment is injected into a container, a composite demulsifier with a mass concentration of 0.25-1% is added, and the mixture is stirred at 400-1200 rpm for 10-30 min, and then heated to 50-70°C, and ultrasonic standing waves are applied with a frequency of 10-40 kHz and an ultrasonic power of 200-350 W, and the ultrasonic treatment time is 3-10 min; After ultrasound, the mixture was allowed to stand for stratification. The lower layer was scum wastewater containing a composite demulsifier, which was subjected to wastewater post-treatment after separation. The upper oil phase was preliminarily dehydrated oily scum, which was subjected to scum post-treatment after separation.
7. The oily scum treatment process according to claim 5, characterized in that: The wastewater post-treatment method is: Add H2O2 with a concentration of 100-200mL / L to the scum wastewater containing the composite demulsifier obtained in step 2), then apply ultrasonic standing wave with a frequency of 30-65kHz, an ultrasonic power of 300-400W, and an ultrasonic treatment time of 30-90min; filter, recover the filter residue, and the filtrate is the treated wastewater.
8. The oily scum treatment process according to claim 5, characterized in that: The scum post-treatment method is: the preliminary dehydrated oily scum obtained in step 2) is separated into oil, water and mud residue in a three-phase horizontal spiral centrifuge, the oil phase product and the water phase product are recycled, and the mud residue product is discharged for further post-treatment.
Citation Information
Patent Citations
Preparation method of magnetic recoverable heavy oil emulsion demulsifier
CN118546694A
Graphene-based nanodemulsifier
US20240217827A1